PENGARUH LATIHAN SIDE TO SIDE BOX SHUTTLE TERHADAP EXPLOSIVE POWER OTOT TUNGKAI PADA PERMAINAN BULUTANGKIS U 13-15 CLUB PB ANGKASA PEKANBARU - Abdillah, Bagus Primanda; Ramadi, Ramadi; Vai, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : Based on that matter, the researcher has decided to give Side to Side Box Shuttle training. This study is intended to discover whether there is some impact of Side to Side Box Shuttle Exercise on Leg Muscle Explosive Power as Seen in Badminton Game U 13-15 Club Pb Angkasa Pekanbaru.Therefore, when conducting the jump for smashing, the athletes can get maximum result. This research is an experimental research by using male badminton athletes U 13-15 Club PB Angkasa Pekanbaru as the population; and the data in this research is all population as many as 5 people.The instrument that is used in this research is the vertical power jump test, which aims to measure the height of the jump. After that, the data is processed statistically to examine the normality with Liliefors test on significant level Î± (0.05). The hypothesis proposed is that there is some effect on Side to Side Box Shuttle Exercise on Leg Muscle Explosive Power. Based on the analysis of statistic data, the writer has discovered that the pre-test average is 8.18 and the average of post-test is 8.81, therefore, those data are normal with the improvement as many as 0.63. According to T test analysis, comes the result that Tcount as 3,15 andTtable as 2,132, which means Tcount>Ttable .As a result, the writes finds out that there is some effects of Side to Side Box Shuttle Exercise on Leg Muscle Explosive Power as seen In Badminton Game U 13-15 Club Pb Angkasa Pekanbaru.Keywords : Side to Side Box Shuttle, Leg Muscle Explosive Power